Industry 4.0, AI and Big Data: Technological Progress and Ethical Responsibilities - Vickers, Tara; Ketel, Mohammed (Transactions on Engineering and Computing Sciences, 2025)
Marking a new phase in digital transformation, Industry 4.0—also referred to as the Fourth Industrial Revolution—incorporates advanced technologies like IoT, AI, Big Data, robotics, cloud computing, and cybersecurity to revolutionize production systems, making them smarter, more efficient, and more flexible. The convergence of these technologies offers significant potential to improve efficiency, reduce operational costs, and enhance customization, while also introducing ethical challenges such as privacy breaches, cybersecurity risks, and algorithmic bias. This paper is structured into two parts: the first part explores Industry 4.0 and its associated technologies, including AI and Big Data; the second part examines the ethical implications of these technologies.